Analyses of balance and flexibility of obese patients undergoing bariatric surgery - Benetti, Fernanda Antico (Clinics (Sao Paulo), 2016)
OBJECTIVE: To assess the postural control and flexibility of obese subjects before and both six and 12 months after bariatric surgery. To verify whether postural control is related to flexibility following weight reductions resulting from bariatric surgery. METHODS: The sample consisted of 16 subjects who had undergone bariatric surgery. All assessments were performed before and six and 12 months after bariatric surgery. Postural balance was assessed using an Accusuway(®) portable force platform, and flexibility was assessed using a standard chair sit and reach test (Wells' chair). RESULTS: With the force platform, no differences were observed in the displacement area or velocity from the center of pressure in the mediolateral and anteroposterior directions. The displacement speed from the center of pressure was decreased at the six month after the surgery; however, unchanged from baseline at 12 months post-surgery. Flexibility increased over time according to the three measurements tested. CONCLUSIONS: Static postural balance did not change. The velocity of postural adjustment responses were increased at six months after surgery. Therefore, weight loss promotes increased flexibility. Yet, improvements in flexibility are not related to improvements in balance.